Audience research of domestic television series - Simeunović Bajić, Nataša (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
TV series have been filmed in Yugoslavia for an increasingly large television audience. TV series are an authentic television genre developed gradually with the spread of the influence of new audio-visual mass media. The production of Television Belgrade was the most prolific one. Domestic TV shows fought for the right over imported TV series program, and great creative force was invested into their making. However, Radio Television of Serbia (RTS) continued the production of domestic TV series in different economic and social conditions. As part of the program offer of the public media service, domestic shows still attract a large audience even in the apparent dominance of the Internet and the diverse offer of national and cable television. Rerunning domestic television series, which is a recognizable feature of Television Belgrade, plays a special role in contemporary television life. Thus, this paper focuses on researching audience of domestic TV series, and especially the representative ones, made during the golden age (1970−1976), during the crisis of the Yugoslav state and society and its collapse (1987−1995) and during the period of post-conflict transitional Serbia after Milošević (2000−2010). These shows include Više od igre (More than a game), Otpisаni (The Sacrificied), Grlom u jаgode (Headless Rush), Ljubаv nа seoski nаčin (Rural Style Love), Bolji život (Better Life) and Rаnjeni orаo (The Wounded Eagle). The aim of the research is to establish general characteristics of the audience of domestic TV series (who watches them, how much and how). Further, it also to provides an in-depth understanding of the ways in which these characteristics and viewers’ preferences participate in the everyday ritual activity of watching series, as an important social practice that represents a segment of formation of cultural needs and cultural identity.
Keywords: television discourse; television genre; Television Belgrade; audience; TV series